(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2012)
After an introduction about recent studies concerning the settlement of Spina, this paper presents the analysis of about 100 amphorical finds therein rescued in 1966. Autoptical analysis identified nine ceramic sample-groups, corresponding to Greek productions (mainly Corinthian, but also Chios, North-Aegean and Attic types: in particular Attic à la brosse amphora represents so far an unicum in Spina’s finds), Graeco-Italic and local productions too. This contribution ends with some considerations about Adriatic trade courses during Late Iron Age, suggested by other materials, such as Greek Plain Cooking Wares, recently identified in Spina’s settlement.